Understanding and managing the food-energy-water nexus – opportunities for water resources research. (January 2018) - Cai, Ximing; Wallington, Kevin; Shafiee-Jood, Majid; Marston, Landon
Highlights: FEW shares IWRM spirit, yet offers a clearer path to research and implementation. Knowledge gaps exist in process, system, technology, and policy linking water with food and energy. FEW provides a context for water researchers to utilize and extend disciplinary strengths. Abstract: Studies on the food, energy, and water (FEW) nexus lay a shared foundation for researchers, policy makers, practitioners, and stakeholders to understand and manage linked production, utilization, and security of FEW systems. The FEW nexus paradigm provides the water community specific channels to move forward in interdisciplinary research where integrated water resources management (IWRM) has fallen short. Here, we help water researchers identify, articulate, utilize, and extend our disciplinary strengths within the broader FEW communities, while informing scientists in the food and energy domains about our unique skillset. This paper explores the relevance of existing and ongoing scholarship within the water community, as well as current research needs, for understanding FEW processes and systems and implementing FEW solutions through innovations in technologies, infrastructures, and policies. Following the historical efforts in IWRM, hydrologists, water resources engineers, economists, and policy analysts are provided opportunities for interdisciplinary studies among themselves and in collaboration with energy and food communities, united by a common path to achieve sustainability development goals.